Answer:
x = -1/2 , 4
Step-by-step explanation:
1) If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
2x+1=0
x−4=0
2) Set the first factor equal to 0.
2x+1=0
3) Subtract 1 from both sides of the equation.
2x=−1
4) Divide each term by 2 and simplify.
2x/2= −1/2
5) Cancel the common factor of 2.
x= −1/2
6) Move the negative in front of the fraction.
x = −1/2
7) Set the next factor equal to 0 and solve.
x=4
8) The final solution is all the values that make
(2x+1)(x−4) = 0 true.
9) x = −1/2 , 4
Answer:
The slope of the line between these two points is 1.50.
Step-by-step explanation:
The general form of the regression line is:
![y=mx+c](https://tex.z-dn.net/?f=y%3Dmx%2Bc)
Here,
<em>y</em> = dependent variable
<em>x</em> = independent variable
<em>m</em> = slope
<em>c</em> = intercept.
The formula to compute slope using two-point method is:
![m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
In this case the dependent variable is the cost per week to feed and independent variable is the weight of the hamster.
The two points are:
(<em>x</em>₁, <em>y</em>₁) = (3, 3.50)
(<em>x</em>₂, <em>y</em>₂) = (4.8, 6.20)
Compute the slope as follows:
![m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
![=\frac{6.20-3.50}{4.8-3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B6.20-3.50%7D%7B4.8-3%7D)
![=\frac{2.7}{1.8}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2.7%7D%7B1.8%7D)
![=1.50](https://tex.z-dn.net/?f=%3D1.50)
Thus, the slope of the line between these two points is 1.50.
Answer:
See below.
Step-by-step explanation:
Total = 110
Let calls on third evening = x
second evening = 4x
first evening = x + 8
=> x + 4x + x + 8 = 110
=> 6x = 102
=> x = 17
First evening = x = 17 calls
Second evening = 4x = 68 calls
Third evening = x + 8 = 25 calls
Answer:
sln
f(x) =-22+x+14 put 2 in x
f(2)=-22+2+14
f(2) =38
Answer:
Number 3 has no solution
Step-by-step explanation:
First you need to divide both sides of the equation 12x - 12y = -12 by 4
-3x + 3y = -3
12x - 12y = -12
-3x + 3y = -3
3x - 3y = -3
Then you need to eliminate one variable by adding the equations.
0 = -6
this statement is false, and therefore has no solution.